Method for extracting aluminum oxide

By mixing and roasting pulverized coal furnace fly ash with calcium chloride dihydrate, and then performing acid treatment and impurity removal roasting twice, the problem of difficulty in extracting high-purity alumina in the existing technology was successfully solved, and the process was simplified and The cost reduction promotes the comprehensive utilization of fly ash.

CN119330382APending Publication Date: 2025-01-21SHENHUA ZHUNNENG RESOURCE COMPREHENSIVE DEV COMPANY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411495224.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently extract high-purity alumina from coal pulverized furnace fly ash, and the process is complex and costly, making it difficult to achieve the comprehensive utilization of fly ash.

Method used

After mixing and roasting the starting raw materials (pulverized coal furnace fly ash, etc.) with calcium chloride dihydrate, acid treatment is performed twice to perform decalcification and alumina dissolution respectively, followed by impurity removal and roasting of the alumina solution. , to obtain high-purity alumina.

Benefits of technology

It achieves efficient extraction of high-purity alumina from fly ash of pulverized coal furnaces, simplifies the process, reduces production costs, and promotes the comprehensive utilization of fly ash resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330382A_ABST
    Figure CN119330382A_ABST
Patent Text Reader

Abstract

The invention provides a method for extracting aluminum oxide. The method comprises the following steps: S1, uniformly mixing an initial raw material with calcium chloride dihydrate, roasting, and crushing to obtain clinker; s2, adding acid into the clinker for the first time, and performing solid-liquid separation to obtain an alumina-containing filter cake and a calcium-containing solution; s3, adding acid into the alumina-containing filter cake for the second time, and carrying out solid-liquid separation to obtain an alumina solution and white mud; s4, sequentially performing impurity removal and roasting on the aluminum oxide solution to obtain aluminum oxide; wherein the initial raw materials comprise one or more of pulverized coal furnace fly ash, anorthite, coal gangue, low-grade bauxite and clay ore. The method comprises the following steps: mixing and crushing an initial raw material and a roasting activator calcium oxide dehydrate, adding acid twice, respectively performing decalcification and aluminum oxide dissolution, removing impurities from the obtained aluminum oxide solution, and roasting to obtain aluminum oxide with relatively high purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste recycling, and in particular to a method for extracting aluminum oxide. Background Art

[0002] According to the different combustion temperatures, fly ash can be divided into circulating fluidized bed fly ash and pulverized coal furnace fly ash. The formation temperature of circulating fluidized bed fly ash is about 840℃, and the main phase composition is amorphous phase. The alumina in the fly ash is highly active and can be directly extracted with acid; the formation temperature of pulverized coal furnace fly ash is about 1300℃, and the mineral mixture is mainly composed of mullite, containing a small amount of quartz and corundum, with poor activity. It is difficult to directly extract the alumina from it with acid, and it needs to be activated before acid leaching.

[0003] The industrial production of alumina from fly ash is mainly based on the traditional alkaline process. However, due to the low aluminum-silicon ratio in the ash, a large amount of silica is dissolved under alkaline conditions, making it difficult to separate silicon and aluminum, and the production cost is high and the amount of slag is large. With the advancement of modern material technology, industrial demonstration projects for extracting alumina from fly ash by acid method have gradually emerged in recent years, but the raw material used is circulating fluidized bed fly ash. The emission of fly ash from pulverized coal furnace is about 9 times that of circulating fluidized bed fly ash. Therefore, only by realizing the comprehensive utilization of fly ash from pulverized coal furnace can the comprehensive utilization of fly ash be truly realized.

[0004] At present, the main technical routes for extracting alumina from fly ash of pulverized coal furnace by acid method after activation are ammonium sulfate activation-hydrochloric acid leaching, such as Chinese patent application document CN106966415A; calcium chloride activation-sulfuric acid leaching, such as Chinese patent application document CN102502729A. The above methods have the disadvantages of difficulty in impurity removal and difficulty in industrialization. It can be seen that only by studying a method for extracting alumina from fly ash of pulverized coal furnace with simple process, broad technology and low cost can the comprehensive utilization of fly ash resources be truly realized and the shortage of bauxite resources in my country be alleviated. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for extracting aluminum oxide, so as to solve the problem that it is difficult to extract high-purity aluminum oxide from fly ash of a pulverized coal furnace in the prior art.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for extracting alumina, comprising the following steps: S1, uniformly mixing a starting raw material with calcium chloride dihydrate, calcining and then crushing to obtain a clinker; S2, adding acid to the clinker for the first time, separating the solid and the liquid, and obtaining a filter cake containing alumina and a solution containing calcium; S3, adding acid to the filter cake containing alumina for the second time, separating the solid and the liquid, and obtaining an alumina solution and white mud; S4, successively removing impurities and calcining the alumina solution to obtain alumina; wherein the starting raw material comprises one or more of fly ash from a pulverized coal furnace, calcium feldspar, coal gangue, low-grade bauxite and clay ore.

[0007] Furthermore, the starting material in S1 is fly ash from a pulverized coal furnace.

[0008] Further, the mass ratio of fly ash from pulverized coal furnace and calcium chloride dihydrate in S1 is 1:0.6-10; more preferably, the mass ratio of fly ash from pulverized coal furnace and calcium chloride dihydrate is 1:0.6-2.0; preferably, the roasting temperature in S1 is 800-1300°C, and the roasting time is 1-6h; more preferably, the roasting temperature in S1 is 900-1100°C, and the roasting time is 2-4h; preferably, the particle size of the clinker in S1 is 40-200μm.

[0009] Further, the acid added during the first acid addition in S2 includes an organic acid or an inorganic acid; preferably, the acid added during the first acid addition in S2 is an inorganic acid; preferably, when the acid is an inorganic acid, the acid is hydrochloric acid, and the mass fraction of the hydrochloric acid is 0.1-38%; more preferably, the mass fraction of the hydrochloric acid is 1-10%; preferably, in terms of molar ratio, the molar ratio of hydrochloric acid to the calcium element in the clinker is 0.8-1.2:1; more preferably, the molar ratio of hydrochloric acid to the calcium element in the clinker is 0.8-1:1; preferably, when the acid is an organic acid, the acid is acetic acid, and the mass fraction of the acetic acid is 30-60%; more preferably, the mass fraction of the acetic acid is 35-45%; preferably, in terms of molar ratio, the molar ratio of acetic acid to the calcium element in the clinker is 1-8:1; more preferably, the molar ratio of acetic acid to the calcium element in the clinker is 2-5:1.

[0010] Furthermore, the solid-liquid separation in S2 includes: performing plate and frame filtration or disk filtration on the product after the first acid addition to obtain a crude alumina filter cake and a calcium-containing solution; washing the crude alumina filter cake to obtain an alumina filter cake; preferably, washing is performed using evaporated condensed water with a mass of 0.5-10 times the mass of the crude alumina filter cake; more preferably, washing is performed using evaporated condensed water with a mass of 1-2 times the mass of the crude alumina filter cake.

[0011] Furthermore, the calcium-containing solution obtained in S2 is concentrated to obtain calcium-containing crystals for use in step S1; preferably, the concentration is evaporative crystallization; preferably, the evaporative crystallization temperature is 60-130° C., and the evaporative crystallization pressure is -0.08-1.1 Mpa.

[0012] Furthermore, the acid added in the second acid addition in S3 is hydrochloric acid; preferably, the mass fraction of hydrochloric acid is 10-30%; more preferably, the mass fraction of hydrochloric acid is 20-28%; preferably, the reaction temperature of the second acid addition is 60-180°C, and the reaction time of the second acid addition is 0.5-6h; more preferably, the reaction temperature of the second acid addition is 70-150°C, and the reaction time of the second acid addition is 2-4h.

[0013] Further, the impurity removal in S4 includes: removing impurities from the alumina solution, and crystallizing the solution after impurity removal to obtain crystalline alumina; preferably, the impurity removal is to extract and remove impurities from the alumina solution, and then perform resin impurity removal; preferably, when performing extraction impurity removal, the extract used includes N, N'-dimethylheptylacetamide or tributyl phosphate; preferably, when performing resin impurity removal, the resin used includes weakly basic anionic calcium removal resin; preferably, the weakly basic anionic calcium removal resin is a resin with primary amino functional groups; preferably, crystallization includes evaporation crystallization or salting-out crystallization; preferably, the evaporation crystallization temperature is 0-100°C, and the evaporation crystallization pressure is -0.02 to -0.2Kpa; more preferably, the evaporation crystallization temperature is 20-50°C, and the evaporation crystallization pressure is -0.05 to -0.1kpa.

[0014] Furthermore, the calcination temperature in S4 is 200-1200° C., and the calcination time is 2-5 h.

[0015] Furthermore, the roasting in S4 generates hydrogen chloride gas, which is recovered and used in the acid addition reaction process of S2 and S3, or in the salting-out crystallization process of S4.

[0016] By applying the technical scheme of the present invention, the starting raw material and the roasting activator calcium oxide dihydrate are mixed and crushed, and then acid is added twice to respectively perform decalcification and aluminum oxide dissolution, and the obtained aluminum oxide solution is decontaminated and then roasted to obtain aluminum oxide with higher purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 A process flow chart for extracting alumina in a preferred embodiment of the present application is shown. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] As mentioned in the background technology, the fly ash from pulverized coal furnace is mainly composed of mullite, containing a small amount of quartz and corundum, with poor activity. It is difficult to directly extract the alumina therein with acid, and it needs to be activated and then leached with acid. With the advancement of modern material technology, industrial demonstration projects for extracting alumina from fly ash by acid method have gradually emerged in recent years, but the raw materials used are mostly circulating fluidized bed fly ash with good alumina activity. The emission of fly ash from pulverized coal furnace is about 9 times that of circulating fluidized bed fly ash. Therefore, only the comprehensive utilization of fly ash from pulverized coal furnace can be the comprehensive utilization of fly ash in the true sense. However, the process technology route of extracting alumina by acid method after activation of fly ash from pulverized coal furnace has the disadvantages of difficulty in removing impurities and difficulty in industrialization. Therefore, the inventor of this application proposes a method for extracting alumina from fly ash from pulverized coal furnace with simple process, broad technology and low cost, so as to realize the comprehensive utilization of fly ash resources.

[0021] In addition, the method for extracting alumina of the present application is also applicable to calcium feldspar, coal gangue, low-grade bauxite and clay ore. The above minerals have similar elemental compositions, such as silicon, aluminum, iron, calcium, magnesium, etc. In the conventional alumina extraction process, a large amount of impurities that are difficult to remove will be generated, resulting in a low purity of the extracted alumina. The technical solution of the present application can also be used to extract alumina from the above ore materials with high purity to achieve comprehensive utilization of mineral resources.

[0022] In the first typical embodiment of the present application, a method for extracting alumina is provided, comprising the following steps: S1, mixing the starting material and calcium chloride dihydrate uniformly, calcining and then crushing to obtain clinker; S2, adding acid for the first time in the clinker, separating the solid and liquid, obtaining a filter cake containing alumina and a solution containing calcium; S3, adding acid for the second time in the filter cake containing alumina, separating the solid and liquid, obtaining alumina solution and white mud; S4, removing impurities and calcining the alumina solution in sequence to obtain alumina; wherein the starting material comprises one or more of pulverized coal furnace fly ash, calcium feldspar, coal gangue, low-grade bauxite and clay ore. The starting material is calcined to activate the alumina component therein, and after crushing to increase its reaction surface area, a first acid-adding decalcification reaction is carried out to initially obtain a filter cake containing alumina, and then a second acid-adding alumina dissolution reaction is carried out on it, and the dissolved alumina solution is removed impurities and calcined to obtain the final alumina solid.

[0023] The above starting material is fly ash from a pulverized coal furnace. Alumina can be extracted from fly ash from a pulverized coal furnace with a large emission volume. The method of the present application can be used to extract alumina from fly ash from a pulverized coal furnace with poor alumina activity, thereby realizing comprehensive utilization of fly ash resources.

[0024] Any mass ratio of fly ash from a pulverized coal furnace to calcium chloride dihydrate is applicable to the present application. In a preferred embodiment, the mass ratio of fly ash from a pulverized coal furnace to calcium chloride dihydrate is 1:0.6-10; more preferably, the mass ratio of fly ash from a pulverized coal furnace to calcium chloride dihydrate is 1:0.6-2.0. Adjusting the mass ratio of fly ash from a pulverized coal furnace to calcium chloride dihydrate is particularly important for the subsequent efficient extraction of aluminum oxide from the fly ash from a pulverized coal furnace. The use of reactants in an appropriate ratio for reaction can better activate the aluminum oxide in the fly ash from a pulverized coal furnace.

[0025] Any reaction temperature and time for calcining the above mixture is applicable to the present application. In a preferred embodiment, the calcination temperature in S1 is 800-1300°C and the calcination time is 1-6h; more preferably, the calcination temperature in S1 is 900-1100°C and the calcination time is 2-4h. On the basis of achieving complete reaction, selecting a suitable calcination temperature and time can reduce the energy consumption of the method.

[0026] Clinker of any particle size is applicable to the present application. In a preferred embodiment, the particle size of the clinker in S1 is 40-200 μm. Crush the clinker to a certain extent to increase the reaction area in the subsequent reaction and complete the reaction more completely.

[0027] The acid added in the first acid addition in S2 above includes an organic acid or an inorganic acid. The first acid addition is to remove the calcium-containing impurities in the above clinker. Any type of acid that can remove calcium impurities in the clinker is applicable to the present application. In a preferred embodiment, the acid added in the first acid addition in S2 is an inorganic acid. Any inorganic acid that can react in S2 and its addition amount are applicable to the present application. In a preferred embodiment, the inorganic acid is hydrochloric acid, and the mass fraction of hydrochloric acid is 0.1-38%; more preferably, the mass fraction of hydrochloric acid is 1-10%. In terms of molar ratio, the molar ratio of hydrochloric acid to calcium in the clinker is 0.8-1.2:1; more preferably, the molar ratio of hydrochloric acid to calcium in the clinker is 0.8-1:1. The hydrochloric acid used in the first acid addition reaction, its mass fraction and addition amount have a certain influence on the subsequent extraction of alumina. The first acid addition using the parameters within the above preferred range can ensure the maximum possible removal of calcium in the clinker.

[0028] When the acid is an organic acid, any organic acid that can be used for the acid addition reaction in S2, and its mass fraction and addition amount are suitable for this application. In a preferred embodiment, the organic acid is acetic acid, and the mass fraction of acetic acid is 30-60%; more preferably, the mass fraction of acetic acid is 35-45%. In terms of molar ratio, the molar ratio of acetic acid to calcium in the clinker is 1-8:1; more preferably, the molar ratio of acetic acid to calcium in the clinker is 2-5:1. If an organic acid is used, a better impurity removal effect can be obtained by reacting with the above parameters.

[0029] The solid-liquid separation in S2 includes: performing plate-and-frame filtration or disk filtration on the product after the first acid addition to obtain a crude alumina filter cake and a calcium-containing solution; washing the crude alumina filter cake to obtain an alumina filter cake. After the first acid addition and calcium removal reaction is completed, the reactants are subjected to solid-liquid separation. Among them, plate-and-frame filtration can cause the filtrate to pass through the filter membrane and be discharged through the working pressure on the liquid containing less residue, and the residue remains in the frame to form a filter cake to complete the solid-liquid separation; disk filtration is performed by a device of several horizontal annular filter discs for solid-liquid separation, which is carried out step by step through the filter discs in the horizontal direction, and the filtrate is extracted by a vacuum device to obtain a solid filter cake.

[0030] Any amount of evaporated condensed water that can achieve washing and impurity removal is applicable to this application. In a preferred embodiment, washing is performed with evaporated condensed water having a mass of 0.5-10 times the mass of the crude alumina-containing filter cake; more preferably, washing is performed with evaporated condensed water having a mass of 1-2 times the mass of the crude alumina-containing filter cake. Based on the consideration of green conservation of the extraction method of this application, as little evaporated condensed water as possible is used for washing while achieving the washing purpose.

[0031] The calcium-containing solution obtained in S2 is concentrated to obtain calcium-containing crystals for use in step S1. The calcium-containing solution is reused for a second time, which reduces the amount of reactants used and improves the efficiency of the method of the present application, thereby maximizing the utilization of the reaction raw materials.

[0032] Any of the above operations that can concentrate the calcium-containing solution is applicable to the present application. In a preferred embodiment, the concentration is evaporation crystallization. And any temperature and pressure that can complete evaporation crystallization are applicable to the present application. In a preferred embodiment, the temperature of evaporation crystallization is 60-130°C and the pressure of evaporation crystallization is -0.08-1.1Mpa.

[0033] The acid added in the second acid addition in S3 is hydrochloric acid. The secondary acid addition is used to carry out an acid dissolution reaction on the filter cake containing aluminum oxide, and insoluble impurities such as white mud after the reaction are removed.

[0034] Any concentration of hydrochloric acid added to the acid dissolution reaction of S3 is applicable to the present application. In a preferred embodiment, the mass fraction of hydrochloric acid is 10-30%; more preferably, the mass fraction of hydrochloric acid is 20-28%. The hydrochloric acid used here can completely react the reactable substances in the alumina-containing filter cake, and the mass fraction of hydrochloric acid can be adjusted from the perspective of cost and efficiency of the method.

[0035] Any reaction temperature and time in the acid dissolution reaction of S3 above are applicable to the present application. In a preferred embodiment, the reaction temperature of the second acid addition is 60-180°C, and the reaction time of the second acid addition is 0.5-6h; more preferably, the reaction temperature of the second acid addition is 70-150°C, and the reaction time of the second acid addition is 2-4h. The reaction temperature of this step determines the reaction efficiency and energy cost of the method of the present application. Therefore, the selection of appropriate reaction temperature and time has a certain influence on the extraction efficiency of aluminum oxide in the method of the present application.

[0036] The impurity removal in S4 above includes: removing impurities from the alumina solution, and crystallizing the solution after impurity removal to obtain crystalline alumina. Any operation that can remove impurities from the alumina solution is applicable to the present application. In a preferred embodiment, the impurity removal is to perform extraction and impurity removal on the alumina solution, and then perform resin impurity removal. The extraction impurity removal is to use an extracting liquid with relevant functions to remove iron from the alumina solution, and the resin impurity removal is to use a negatively charged resin to remove calcium impurities to obtain an alumina solution with most impurities removed.

[0037] When performing extraction and impurity removal, any extractant that can remove iron impurities in the alumina solution is suitable for this application. In a preferred embodiment, the extractant used includes N, N'-dimethylheptylacetamide or tributyl phosphate. When performing resin impurity removal, any resin that can remove calcium impurities in the alumina solution is suitable for this application. In a preferred embodiment, the resin used includes a weakly basic anionic calcium removal resin. In a preferred embodiment, the weakly basic anionic calcium removal resin is a resin with a primary amino functional group. Due to electrostatic effects, the anions carried by the resin particles can adsorb calcium ions to the resin surface, thereby reducing the calcium resin content in the solution. After elution, the calcium element enters the solution, and the calcium resin resumes its adsorption function.

[0038] Any operation that can crystallize the impurity-removed alumina solution is applicable to the present application. In a preferred embodiment, the crystallization includes evaporation crystallization or salting-out crystallization. When the impurity-removed alumina solution is crystallized by evaporation crystallization, in a preferred embodiment, the evaporation crystallization temperature is 0-100°C, and the evaporation crystallization pressure is -0.02 to -0.2Kpa; more preferably, the evaporation crystallization temperature is 20-50°C, and the evaporation crystallization pressure is -0.05 to -0.1kpa. The above-mentioned evaporation crystallization temperature and pressure selection can save the energy consumption in the method of the present application.

[0039] Any temperature and time that can be used to calcine the crystalline alumina are applicable to the present application. In a preferred embodiment, the calcination temperature in S4 is 200-1200°C and the calcination time is 2-5 hours. The calcination at this stage evaporates the water in the crystalline alumina to obtain alumina solid. Selecting a suitable calcination temperature and time can reduce the energy consumption of the method.

[0040] The roasting in S4 generates hydrogen chloride gas, which is recycled and used in the acid addition reaction process of S2 and S3, or in the salting-out crystallization process of S4. The byproduct hydrogen chloride gas in the reaction in S4 is recycled and reused, which not only saves materials but also improves the implementation efficiency of the method of the present application, and can maximize the utilization of the reaction raw materials.

[0041] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0042] The fly ash used in the embodiment is the fly ash of high-aluminum pulverized coal furnace discharged by a certain power plant, and the specific composition is as follows:

[0043] Table 1 Fly ash composition

[0044] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[Fe2O3]]> <![CDATA[TiO2]]> <![CDATA[SO4]]> LOI Mass fraction / % 39.76 48.10 2.24 1.25 1.98 1.2 1.75 3.3

[0045] Embodiment 1 (with Figure 1 Prepared according to the process shown)

[0046] The fly ash from the pulverized coal furnace and calcium chloride dihydrate are mixed in a blender at a mass ratio of 1:1.5, and then roasted at a temperature of 1100°C for 2 hours. The resulting clinker is crushed to 100 μm, and the resulting clinker is decalcified and solid-liquid separated to obtain an alumina filter cake and a calcium solution. When the clinker is decalcified, the mass fraction of hydrochloric acid is 8%, and the molar ratio of acid to calcium in the roasted clinker is 1:1. After decalcification and dissolution, the slurry is filtered by plate and frame filtration, and the filter cake is washed with 2 times evaporated condensed water. When the alumina filter cake is subjected to the second acid dissolution, the hydrochloric acid concentration is 28%, the dissolution temperature is 90°C, and the dissolution time is 2 hours. After solid-liquid separation of the filter cake and hydrochloric acid, aluminum chloride solution and white mud are obtained; the aluminum chloride solution is first extracted and impurities are removed, and the extraction liquid used is N, N'-dimethylheptylacetamide, and then impurities are removed by resin, and the resin used is a primary aminosulfonic acid type cation exchange resin to obtain aluminum chloride refined liquid, which is evaporated and crystallized at a crystallization temperature of 40°C to obtain crystalline aluminum chloride; the crystalline aluminum chloride is roasted at 1000°C for 4 hours to obtain aluminum oxide.

[0047] The calcium-containing solution is evaporated, crystallized and concentrated, and the obtained calcium-containing crystals are reused as a roasting activator. The temperature of the evaporation crystallization is 130° C., and the pressure of the evaporation crystallization is -0.08 Mpa.

[0048] Example 2

[0049] The fly ash from the pulverized coal furnace and calcium chloride dihydrate are mixed in a blender in a mass ratio of 1:2, and then roasted at a temperature of 1100°C for 2 hours. The resulting clinker is crushed to 100 μm, and the resulting clinker is decalcified and solid-liquid separated to obtain an alumina filter cake and a calcium solution. When the clinker is decalcified, the mass fraction of hydrochloric acid is 10%, and the molar ratio of acid to calcium in the roasted clinker is 0.8:1. After decalcification and dissolution, the slurry is filtered by plate and frame filtration, and the filter cake is washed with 2 times evaporated condensed water. When the alumina filter cake is subjected to the second acid dissolution, the hydrochloric acid concentration is 28%, the dissolution temperature is 150°C, and the dissolution time is 3 hours. After solid-liquid separation of the filter cake and hydrochloric acid, aluminum chloride solution and white mud are obtained; the aluminum chloride solution is first extracted and impurities are removed, and the extraction liquid used is N, N'-dimethylheptylacetamide, and then impurities are removed by resin, and the resin used is a primary aminosulfonic acid type cation exchange resin to obtain aluminum chloride refined liquid, which is evaporated and crystallized at a crystallization temperature of 40°C to obtain crystalline aluminum chloride; the crystalline aluminum chloride is roasted at 1000°C for 4 hours to obtain aluminum oxide.

[0050] The calcium-containing solution is evaporated, crystallized and concentrated, and the obtained calcium-containing crystals are reused as a roasting activator. The temperature of the evaporation crystallization is 130° C., and the pressure of the evaporation crystallization is -0.08 Mpa.

[0051] Example 3

[0052] The fly ash from the pulverized coal furnace and calcium chloride dihydrate are mixed in a blender at a mass ratio of 1:0.6, and then roasted at a temperature of 1100°C for 2 hours. The resulting clinker is crushed to 100 μm, and the resulting clinker is decalcified and solid-liquid separated to obtain an alumina filter cake and a calcium solution. When the clinker is decalcified, the mass fraction of hydrochloric acid is 1%, and the molar ratio of acid to calcium in the roasted clinker is 0.9:1. After decalcification and dissolution, the slurry is filtered by plate and frame filtration, and the filter cake is washed with 2 times evaporated condensed water. When the alumina filter cake is subjected to the second acid dissolution, the hydrochloric acid concentration is 28%, the dissolution temperature is 70°C, and the dissolution time is 4 hours. After solid-liquid separation of the filter cake and hydrochloric acid, aluminum chloride solution and white mud are obtained; the aluminum chloride solution is first extracted and impurities are removed, and the extraction liquid used is tributyl phosphate, and then impurities are removed by resin, and the resin used is a primary aminosulfonic acid type cation exchange resin to obtain a refined aluminum chloride solution, which is evaporated and crystallized at a crystallization temperature of 40°C to obtain crystalline aluminum chloride; the crystalline aluminum chloride is roasted at 1000°C for 4 hours to obtain aluminum oxide.

[0053] The calcium-containing solution is evaporated, crystallized and concentrated, and the obtained calcium-containing crystals are reused as a roasting activator. The temperature of the evaporation crystallization is 130° C., and the pressure of the evaporation crystallization is -0.08 Mpa.

[0054] Example 4

[0055] The fly ash from the pulverized coal furnace and calcium chloride dihydrate are mixed in a blender at a mass ratio of 1:6, and then roasted at a temperature of 1300°C for 1 hour. The resulting clinker is crushed to 100 μm, and the resulting clinker is decalcified and solid-liquid separated to obtain an alumina filter cake and a calcium solution. When the clinker is decalcified, the mass fraction of acetic acid is 50%, and the molar ratio of acid to calcium in the roasted clinker is 6:1. After decalcification and dissolution, the slurry is filtered by plate and frame filtration, and the filter cake is washed with 5 times evaporated condensed water. When the alumina filter cake is subjected to the second acid dissolution, the hydrochloric acid concentration is 30%, the dissolution temperature is 180°C, and the dissolution time is 1 hour. After solid-liquid separation of the filter cake and hydrochloric acid, aluminum chloride solution and white mud are obtained; the aluminum chloride solution is first extracted and impurities are removed, and the extraction liquid used is tributyl phosphate, and then impurities are removed by resin, and the resin used is a primary aminosulfonic acid type cation exchange resin to obtain a refined aluminum chloride solution, which is evaporated and crystallized at a crystallization temperature of 10°C to obtain crystalline aluminum chloride; the crystalline aluminum chloride is roasted at 1000°C for 4 hours to obtain aluminum oxide.

[0056] The calcium-containing solution is evaporated, crystallized and concentrated, and the obtained calcium-containing crystals are reused as a roasting activator. The temperature of the evaporation crystallization is 130° C., and the pressure of the evaporation crystallization is -0.08 Mpa.

[0057] Comparative Example 1

[0058] The mass ratio of fly ash from the pulverized coal furnace to calcium chloride dihydrate is 1:12. The remaining steps are the same as those in Example 1.

[0059] Comparative Example 2

[0060] When the acid is added for the first time in S2, the mass fraction of the hydrochloric acid used is 40%, and the molar ratio of the acid to the calcium in the roasted clinker is 2: 1. The remaining steps are the same as those in Example 1.

[0061] Comparative Example 3

[0062] When the acid is added for the second time in S3, the reaction dissolution temperature is 25°C and the dissolution time is 7 hours. The remaining steps are the same as those in Example 1.

[0063] Comparative Example 4

[0064] An experiment was conducted using the method of producing alumina from fly ash in the prior art. The fly ash raw ash was subjected to a strong iron-neodymium-boron magnet to remove iron oxide to obtain de-ironized fly ash; 20 grams of de-ironized fly ash sample, 20 grams of NaOH and 60 ml of water were stirred in a 95°C hydrothermal system for 2 hours, and desiliconized fly ash was obtained by filtration; after drying, it was evenly mixed with 11 grams of anhydrous calcium chloride powder (wherein the mass fraction ratio of calcium chloride to SiO2 in the de-siliconized fly ash was 1.6:1), placed in a 100×100×25 (length×width×height, unit: mm) corundum crucible and roasted at 1000°C for 1 hour; after cooling, it was ground into powder using a mortar and mortar, and washed once with distilled water to remove unreacted calcium chloride; the filter cake was washed with 140 mL of 6M sulfuric acid (fly ash / sulfuric acid mass ratio is 1:4) was leached for 1 hour at a leaching temperature of 30°C, 50ml of water was added for slight dilution, and then filtered, the filter residue was washed once with 100ml of water and combined with the filtrate.

[0065] Test experiment: Comparing the technical effects of Examples 1-4 and Comparative Examples 1-5, the test results are shown in the following table:

[0066] Alumina dissolution rate (%) Alumina purity (%) Example 1 88.2 98.6 Example 2 89.3 98.8 Example 3 90.5 99.1 Example 4 92.2 99.3 Comparative Example 1 76.1 93.2 Comparative Example 2 66.1 86.2 Comparative Example 3 62.5 82.1 Comparative Example 4 73.5 80.4

[0067] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: after the starting raw materials and the roasting activator calcium oxide dihydrate are mixed and crushed in a certain proportion, the impurities such as calcium and iron in the alumina dissolution are removed more thoroughly by adding acid twice, and alumina with higher purity is obtained under low energy consumption, thereby realizing the industrial utilization of fly ash from pulverized coal furnace.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for extracting aluminum oxide, characterized in that: The following steps are involved: S1, mixing the starting material and calcium chloride dihydrate uniformly, roasting and then crushing to obtain clinker; S2, adding acid to the clinker for the first time, separating the solid and the liquid, and obtaining an alumina-containing filter cake and a calcium-containing solution; S3, adding acid for the second time to the alumina-containing filter cake to separate the solid and liquid to obtain an alumina solution and white mud; S4, sequentially removing impurities and calcining the alumina solution to obtain the alumina; The starting raw materials include one or more of fly ash from pulverized coal furnace, calcium feldspar, coal gangue, low-grade bauxite and clay ore.

2. The method according to claim 1, characterized in that The starting material in S1 is fly ash from a pulverized coal furnace.

3. The method according to claim 2, characterized in that The mass ratio of the fly ash from the pulverized coal furnace to the calcium chloride dihydrate in S1 is 1:0.6-10; more preferably, the mass ratio of the fly ash from the pulverized coal furnace to the calcium chloride dihydrate is 1:0.6-2.0; Preferably, the calcination temperature in S1 is 800-1300°C, and the calcination time is 1-6h; more preferably, the calcination temperature in S1 is 900-1100°C, and the calcination time is 2-4h; Preferably, the particle size of the clinker in S1 is 40-200 μm.

4. The method according to claim 1, characterized in that: The acid added during the first acid addition in S2 includes an organic acid or an inorganic acid; preferably, the acid added during the first acid addition in S2 is an inorganic acid; Preferably, when the acid is an inorganic acid, the acid is hydrochloric acid, and the mass fraction of the hydrochloric acid is 0.1-38%; more preferably, the mass fraction of the hydrochloric acid is 1-10%; Preferably, in terms of molar ratio, the molar ratio of the hydrochloric acid to the calcium element in the clinker is 0.8-1.2:1; more preferably, the molar ratio of the hydrochloric acid to the calcium element in the clinker is 0.8-1:1; Preferably, when the acid is an organic acid, the acid is acetic acid, and the mass fraction of the acetic acid is 30-60%; more preferably, the mass fraction of the acetic acid is 35-45%; Preferably, in terms of molar ratio, the molar ratio of the acetic acid to the calcium element in the clinker is 1-8:1; more preferably, the molar ratio of the acetic acid to the calcium element in the clinker is 2-5:

1.

5. The method according to claim 1, characterized in that: The solid-liquid separation in S2 comprises: performing plate-and-frame filtration or plate-and-pan filtration on the product after the first acid addition to obtain a crude alumina-containing filter cake and the calcium-containing solution; washing the crude alumina-containing filter cake to obtain the alumina-containing filter cake; Preferably, the washing is carried out using evaporated condensed water having a mass of 0.5-10 times the mass of the crude alumina-containing filter cake; more preferably, the washing is carried out using evaporated condensed water having a mass of 1-2 times the mass of the crude alumina-containing filter cake.

6. The method according to any one of claims 1 to 4, characterized in that The calcium-containing solution obtained in step S2 is concentrated to obtain calcium-containing crystals which can be used in step S1; Preferably, the concentration is evaporative crystallization; Preferably, the temperature of the evaporation crystallization is 60-130° C., and the pressure of the evaporation crystallization is -0.08-1.1 MPa.

7. The method according to claim 1, characterized in that The acid added in the second acid addition in S3 is hydrochloric acid; Preferably, the mass fraction of the hydrochloric acid is 10-30%; more preferably, the mass fraction of the hydrochloric acid is 20-28%; Preferably, the reaction temperature of the second acid addition is 60-180° C., and the reaction time of the second acid addition is 0.5-6 h; more preferably, the reaction temperature of the second acid addition is 70-150° C., and the reaction time of the second acid addition is 2-4 h.

8. The method according to claim 1, characterized in that The impurity removal in S4 comprises: removing impurities from the alumina solution, and crystallizing the impurity-removed solution to obtain crystalline alumina; Preferably, the impurity removal is to extract and remove impurities from the alumina solution, and then remove impurities from the resin; Preferably, when performing the extraction and impurity removal, the extracting liquid used includes N,N'-dimethylheptylacetamide or tributyl phosphate; Preferably, when performing the resin impurity removal, the resin used includes a weakly alkaline anionic calcium removal resin; Preferably, the weakly alkaline anionic calcium removal resin is a resin with primary amino functional groups; Preferably, the crystallization comprises evaporative crystallization or salting-out crystallization; Preferably, the evaporation crystallization temperature is 0-100°C, and the evaporation crystallization pressure is -0.02 to -0.2 KPa; more preferably, the evaporation crystallization temperature is 20-50°C, and the evaporation crystallization pressure is -0.05 to -0.1 kPa.

9. The method according to claim 1, characterized in that: The calcination temperature in S4 is 200-1200° C., and the calcination time is 2-5 hours.

10. The method according to claim 1, characterized in that The roasting in S4 generates hydrogen chloride gas, and the hydrogen chloride gas is recovered and used in the acid addition reaction process of S2 and S3, or in the salting-out crystallization process of S4.

Citation Information

Patent Citations

  • Method for producing alumina by using pulverized fuel ash

    CN102502729A

  • Process method for extracting aluminum oxide in coal ash of pulverized coal furnace by using acid method

    CN106966415A